2008
DOI: 10.1007/s00335-008-9141-x
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of production-associated DNA polymorphisms in the genes of cattle, goat, sheep, and pig

Abstract: Increasing productivity is one of the main objectives in animal production. Traditional breeding methods have led to increased gains in some traits but gains are not easily attainable in traits with low heritabilities. Exploiting the genetic variations underlying desired phenotypes is the goal of today's animal producers. Such positive genetic variants must, however, be known before possible application. Consequently, candidate genes of traits of interest have been searched for possible relationships with such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 151 publications
1
36
0
3
Order By: Relevance
“…Recently, however, studies have shown that intronic mutations may affect splice sites and consequently mRNA stability, and may lead to truncated or a lack of protein products (Ibeagha-Awemu et al, 2008). Importantly, further studies are needed to determine how the mutations affect phenotypic variation of these traits.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, studies have shown that intronic mutations may affect splice sites and consequently mRNA stability, and may lead to truncated or a lack of protein products (Ibeagha-Awemu et al, 2008). Importantly, further studies are needed to determine how the mutations affect phenotypic variation of these traits.…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente, las pruebas de ADN son herramientas disponibles para los criadores de ganado y todos aquellos interesados en llevar a cabo el monitoreo de la calidad y salud genética de los animales del hato (1,2) . En bovinos, se han descrito pruebas de ADN para identificar portadores de al menos 40 desórdenes genéticos (1,3) .…”
Section: Introductionunclassified
“…En bovinos, se han descrito pruebas de ADN para identificar portadores de al menos 40 desórdenes genéticos (1,3) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It is known that 18 alleles of CSN1S1 gene have been identified so far, which are associated with different expression levels of αS1-CN in milk (Küpper et al, 2010). These alleles can be grouped in four classes: strong alleles (A, B1, B2, B3, B4, B', C, H, L and M) are associated with 3.5 g/L; intermediate alleles (E and I) are associated with 1.1 g/L; weak alleles (F and G) are associated with 0.45 g/L of αS1-CN content; and null alleles (01, 02 and N) are associated with the absence of αS1-CN in milk (Grosclaude et al, 1997;Ramunno et al, 2000;Ibeagha-Awemu et al, 2008;Mastrangelo et al, 2013). As a result, the characterization of the CSN1S1 gene is important owing to its relationship with cheese production and milkprocessing properties (Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%